Blood Coagulation and Thrombosis in Patients with Ovarian Malignancy - von Tempelhoff, Georg-Friedrich; Dietrich, Michael; Niemann, Frank; Schneider, Dirk; Hommel, Gerhard; Heilmann, Lothar (Thrombosis and Haemostasis, 1997)
Ovarian cancer cells appear to be capable of both thrombin formation and induction of fibrin degradation which may be essential prerequisites for the development of deep vein thrombosis (DVT) as well as the spread of malignancy. To study further this coagulation – cancer interaction in 60 patients with untreated ovarian cancer of FIGO stage I-IV the incidence of DVT was recorded pre-operatively, postoperatively on day 1, 3, 5, 7, 10, before each of six cycles of Cisplati- num/Epirubicin/Cyclophosphamide chemotherapy, during follow-up and in the post-operative period of second look surgery. In addition, blood coagulation tests results were determined prospectively. Two patients were excluded from these calculations due to previous DVT 5 to 6 weeks before the diagnosis of ovarian cancer but all patients were eligible for surgery and randomized to receive either daily low molecular weight heparin (LMWH) (n = 28) or unfractionated heparin (UFH) (n = 32) for perioperative thrombosis prophylaxis until the 7th postoperative day. According to the FIGO stage, patients were equally distributed in the 2 heparin treatment groups. The predictive value of pre-operative coagulation test results, clinical parameters, and type of heparin used were tested in univariate and multivariate analysis for development of post-operative DVT and overall patients survival. Impedance plethysmography for DVT screening was used. The presence of DVT was then confirmed by phlebography. Only D-dimer and fibrinogen levels were correlated significantly with the FIGO stage while antithrombin, protein C, and plasminogen activator inhibitor activity were not. The incidence of DVT was 6.7% (4/60) up to the 7th and 8.3% (5/60) between the 8th and 29th post-operative day. DVT occurred in 10.6 % (5/47) during chemotherapy. Pre-operative coagulation test results, the type of heparin used, and clinical parameters were not significant risk factors for post-operative DVT development in univariate analysis. The D-dimer and fibrinogen levels were significant risk factors for reduced overall survival in univariate analysis but only the FIGO stage was an independent predictor (in multivariate analysis). After a median follow up of 26.5 months (min. 8 months, max. 41 months), 21.4% of LMWH treated and 37.5% of UFH-treated patients died of cancer (p = 0.26). Pre-operative test results were neither predictive for DVT nor the outcome of cancer but patients showed an improved though not statistically significant overall survival after LMWH treatment.